Genetic analysis of the diet of red‐footed boobies (Sula sula) provisioning chicks at Ulupa'u Crater, O'ahu. Issue 2 (21st September 2020) - Donahue, Sarah E.; Adams, Josh; Renshaw, Mark A.; Hyrenbach, K. David
Abstract: The diet of red‐footed boobies ( Sula sula ) provisioning chicks was quantified using 106 regurgitations collected from 81 adults over two study years with contrasting oceanographic conditions: 2014 and 2015. A total of 1, 049 prey items were sorted into three broad categories (fish, squid, and other, consisting of highly‐digested 'mush' and parasitic isopods) and assigned a categorical freshness value of 1 (perfect condition), 2 (superficial digestion), or 3 (highly digested and incomplete). A total of 492 undigested prey items (freshness 1 and 2) were measured and sampled for genetic identification with 401 (82%) successfully identified. Rarefaction analyses suggested robust diet sampling, with 32 documented species: 29 fishes and three squids. While the prey‐specific index of relative importance highlighted that fish dominated the diet in 2014 (32.3% fish, 15.1% squid) and in 2015 (29.9% fish, 22.3% squid), diet composition varied significantly between the two study years. The purpleback flying squid ( Stenoteuthis oulaniensis ) accounted for 98.7% (232 of 236) of the identified squid specimens. Mantle lengths were significantly longer in 2015 (7.2 ± 1.1 SD cm) than in 2014 (6.3 ± 1.7 SD cm). These results indicate a higher relative abundance and size of the epipelagic squids available to foraging red‐footed boobies in 2015, during warm‐water conditions associated with the positive phase of the El Niño Southern Oscillation. Due to their diverse diet, red‐footed boobies are useful bioindicators of epipelagic nekton assemblages during changing oceanographic conditions. Moreover, their reliance on the purpleback flying squid makes these seabirds ideal samplers of the juveniles of this poorly studied species. Understanding how interannual and longer‐term oceanographic variability affects central‐place foraging seabirds and the recruitment and abundance of their squid prey is critical for precautionary ecosystem‐based fisheries management of oceanic islands and the surrounding marine environment.